Analisis Kritis Kritik Al-Dzahabi terhadap Tafsir Al-Kasysyaf terhadap Q.S. an-Nisa’: 164 - Rasya' Alfirdaus; Aliyya Qothrunnada AS; M. Sihabudin (Jurnal Studi Al-Qur'an, 2025)
The development of interpretation from era to era has given rise to sectarianism, absolutism, and blind fanaticism in interpretation. This is highly risky and has excellent potential to become a deviation in interpretation, thus giving rise to the study of critical interpretation. In this context, the Tafsir al-Kasysyaf, known for the intense subjectivity of its interpreter, is particularly susceptible to absolutism and blind fanaticism, which are closer to deviations in interpretation. Therefore, it is worthy of critical study. Al-Dzahabi, an expert in critical interpretation, outlines the critical research here. The object of study focuses on Q.S. al-Nisa' verse 164 because it discusses the nature of Allah's speech that the Mu'tazilah opposes, thus providing an overview of how the mufassir defends the theology he adheres to regarding this verse. Using library research and descriptive analysis methods, this research article aims to examine al-Dzahabi's criticism based on the focus of the study on the interpretation of Q.S. al-Nisa' verse 164 in al-Kasysyaf — whether it is included in al-dakhil or not, and about the forms of al-dakhil that contradict al-ashil. This study found that az-Zamakhsyari's interpretation of the verse is categorised as al-dakhil in the form of riwayat and raiso or ijtihad. Further research recommendations include expanding the analysis to other interpretations influenced by theological tendencies and developing a methodology of interpretation criticism as a scientific evaluation tool. This study encourages academics and exegesis practitioners to apply an objective, critical approach to maintain validity and avoid errors in understanding the Quran.